Comparison of altered fractionation schedule with concurrent chemo-radiation for squamous cell carcinoma of head and neck - K., Mathew Varghese; Narayanan, Geeta S.; Vishwanathan, Bhaskar; Karpurmath, Shashidhar V.; Narayanan, Soumya (International Journal of Research in Medical Sciences, 2020)
Background: Aim of the study was to compare the response of altered fractionation schedule with concurrent chemo-radiation in patients with primary and the nodal disease. Methods: Total of 40 patients (20 in each arm) with stage 1- 4 squamous cell carcinoma of the head and neck with a performance status of 0-2 (ECOG) were included in the study. Arm A was altered fractionation schedule where in patients received 6 fractions per week to a total dose of 6600 cGy in 33 fractions. In Arm B, patients received conventional radiotherapy with concurrent chemotherapy three weekly Inj. of cisplatin (100 mg/m2). Patients were evaluated for acute toxicity every week using the Acute Radiation Morbidity Scoring Criteria. The response was assessed after 6 weeks and 12 weeks post treatment using the RECIST criteria. Data was statistically analyzed. Results: Seventeen patients in Arm A and 18 patients in Arm B completed the treatment. At the end of three months, In Arm A, 7 patients had complete response and in Arm B, 9 patients had complete response of the primary (p>0.05). When the complete nodal response was compared in both the arms, there was no difference (2 vs 4 in Arm A vs Arm B resp.). But there were more partial nodal responders in Arm B (p = 0.016). The acute toxicities were comparable in both the arms. Conclusions: Altered fraction radiotherapy can be used in early lesions with minimal nodal burden but with locally advanced disease or large nodal burden addition of chemotherapy should not be avoided.